2004
DOI: 10.1016/j.gca.2004.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Association of calcium with colloidal particles and speciation of calcium in the Kalix and Amazon rivers

Abstract: Abstract-A considerable amount of colloidally bound Ca has been detected in water samples from Amazonian rivers and the Kalix River, a sub-arctic boreal river. Fractionation experiments using several analytical techniques and processing tools were conducted in order to elucidate the matter. Results show that on average 84% of the total Ca concentration is present as free Ca. Particulate, colloidal and complexed Ca constitute the remaining 16%, of which the colloidal fraction is significant. Ultrafiltration exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…Lead et al (1997) have presented a critical review of the different techniques for separation and analysis of colloids (filtration, dialysis, centrifugation, but also voltametry, gels (DET/DGT), field-flow fractionation, SPLITT; Dahlqvist et al, 2004). Ultrafiltration membranes have been developed with nominal cutoff sizes ranging from the thousands of daltons (Da) to hundreds of thousands of daltons, which have been used to separate the colloidal pool into several fractions.…”
Section: Nature Of the Colloidsmentioning
confidence: 99%
“…Lead et al (1997) have presented a critical review of the different techniques for separation and analysis of colloids (filtration, dialysis, centrifugation, but also voltametry, gels (DET/DGT), field-flow fractionation, SPLITT; Dahlqvist et al, 2004). Ultrafiltration membranes have been developed with nominal cutoff sizes ranging from the thousands of daltons (Da) to hundreds of thousands of daltons, which have been used to separate the colloidal pool into several fractions.…”
Section: Nature Of the Colloidsmentioning
confidence: 99%
“…This catchment can therefore be used as a pristine reference system for studies of hydrogeochemical processes in boreal river basins. A number of trace element and isotope studies have previously been performed in this drainage basin (Ponte´r et al, , 1992Ö hlander et al, 1991, 2000Ingri and Widerlund, 1994;Ingri et al, 1997Ingri et al, , 2000Porcelli et al, 1997;Ö hlander, 1997, 2000;Andersson et al, 1998Andersson et al, , 2001Land et al, 1999Dahlqvist et al, 2004). In this study the major element geochemistry is presented.…”
Section: Introductionmentioning
confidence: 98%
“…The Kalix River, an unregulated pristine boreal river system, has previously been well characterized in several studies on major and trace elements and isotopes (Pontér et al, 1990;Ö hlander et al, 1991Ingri and Widerlund, 1994;Ingri et al, 1997Ingri et al, , 2000Ingri et al, , 2005Porcelli et al, 1997;Ö hlander, 1997, 2000;Andersson et al, 1998Andersson et al, , 2001Land et al, 1999aLand et al, ,b, 2000aDahlqvist et al, 2004). The study by Ingri et al (2000) showed that transport of REE in the Kalix River was closely associated with colloidal particles rich in C, Fe and Al.…”
Section: Introductionmentioning
confidence: 99%
“…This study on REE fractionation is part of the 'Kalix 2002' project, in which we have studied temporal changes in the geochemistry of colloids in the Kalix River from winter conditions, through the spring flood event and into summer conditions. Other papers from this project include a study of calcium association with colloids (Dahlqvist et al, 2004), together with studies of multiway analysis of organic matter fluorescence, and of the temporal changes of trace metals associated with colloidal material, which will be presented elsewhere.…”
Section: Introductionmentioning
confidence: 99%